SOCIAL SENSING SENSUS PENDUDUK 2020 PADA JEJARING SOSIAL TWITTER - Aulia Maghfira; Farid Ridho (Seminar Nasional Official Statistics, 2020)
One of important things in organizing the 2020 population census is the spread of information. Twitter becomes suitable media for disseminating information about 2020 population census because the spread of information on twitter not only limited for followers of an account but also for others who are not followers. Twitter users are considered as social sensor, where users will capture information obtained from their surroundings then upload them to twitter. In this research, twitter will be used to see the conversation patterns, information flow, and public participation towards 2020 population census. Descriptive and sentiment analysis will be used to see the conversation patterns. Result shows that there is fluctuating trend. Tweets volume increase significantly when online population census will take place and when President Jokowi sent a tweet to join the population census. Most tweets have neutral sentiment. Social Network Analysis (SNA) is used to see the information flow. Result shows that there are 3 most retweeted accounts: Jokowi; BPS; and sandalista, which is a community account that often sends tweets that contain opinion about government policy. String matching is used to see the public participation towards 2020 population census. Result shows that the proportion of users who send tweets is dominated by nonBPS users by 85.86 percent. This research provides recommendation and can be used as evaluation materials on the spread of information of the 2020 population census.